Landscape Dakwah Islam Kultural Sunan Kalijaga di Jawa - Ngatmin Abbas; Fatah Suparman; Lilis Suryanto; Muhammad Chafidz Ali Wafa (Amorti: Jurnal Studi Islam Interdisipliner, 2023)
This research aims to reveal the role of Sunan Kalijaga as a wali in spreading Islamic teachings in Java through a cultural approach that respects the cultural diversity of the local community. The method used in this research is qualitative with Sunan Kalijaga as the research subject. The data sources used in this research are historical books and religious texts related to Sunan Kalijaga. The data collection techniques used in this research are literature study and documentation. The data analysis technique used is content analysis. The results show that Sunan Kalijaga played an important role in spreading Islamic teachings in Java through a cultural approach by utilizing art and culture, such as wayang, traditional Javanese dances, and songs in his preaching. He taught these dances and songs with Islamic content that was adapted to the Javanese cultural context. Sunan Kalijaga transformed wayang from merely entertainment into a means of preaching and teaching Islamic religion by teaching wayang characters as examples of virtues and role models in Islamic teachings. Based on the results of the research, it is concluded that Sunan Kalijaga played an important role in spreading Islamic teachings in Java through a cultural approach that respects the cultural diversity of the local community. Through the use of art and culture, Sunan Kalijaga strengthened interfaith relationships and instilled the values of tolerance in Java at that time. Therefore, this research suggests that the values taught by Sunan Kalijaga, such as diversity, tolerance, and the use of art and culture as a means of preaching, must be preserved and strengthened as part of Indonesia's cultural heritage.